Validity and reliability of knowledge, attitude, and practice regarding exercise and exergames experiences questionnaire among high school students - Rwayda Abdulkader Mohamed; Nur Arzuar Abdul Rahim; Siti Mardhiana Mohamad; Hazwani Ahmad Yusof (BMC, 2022)
Abstract An instrument to measure the Knowledge, Attitude, and Practice (KAP) related to exercise and exergames experiences among high school students is important to identify the KAP gap that may facilitate the health intervention to boost the immunity of the young population. Thus, our study aims to develop and validate a questionnaire assessing KAP regarding exercise and exergames experiences among high school students. A cross-sectional study was conducted among 188 high school students in Malaysia. This research questionnaire was adapted from a previous study and modified with an additional section to assess high school students' exergames experiences. Content validity, construct validity, and reliability was verified using different tests. Only one item (slimming tea and other drugs could be used in place of exercise to achieve the same effects) did not reach the required level of content validity index in terms of their relevance, clarity, simplicity, and ambiguity. Therefore, this item was removed from the instrument. For factor analysis, three questions were removed from the instrument due to those questions having a factor loading lower than 0.4. The Intraclass Correlation Coefficient values for the test-retest reliability after an interval of two weeks for all questions were > 0.7. Kappa coefficient ranges between 0.67-0.96. The SME value ranged from 0.34 to 1.47. Repeated measured ANOVA did not reveal any significant differences between the test and re-test. This questionnaire has strong validity and reliability that can be used to measure high school student's knowledge, attitude, and practice about exercise and their exergames experiences.